Picorna-Like Viruses of the Havel River, Germany - Zell, Roland; Groth, Marco; Selinka, Lukas; Selinka, Hans-Christoph (Frontiers in Microbiology, 2022)
To improve the understanding of the virome diversity of riverine ecosystems in metropolitan areas, a metagenome analysis was performed with water collected in June 2018 from the river Havel in Berlin, Germany. After enrichment of virus particles and RNA extraction, paired-end Illumina sequencing was conducted and assignment to virus groups and families was performed. This paper focuses on picorna-like viruses, the most diverse and abundant group of viruses with impact on human, animal and environmental health. Here, we describe altogether 166 viral sequences ranging in size from 1 to 11.5 kb. The 71 almost complete genomes are comprised of one candidate iflavirus, one picornavirus, two polycipiviruses, 27 marnaviruses, 27 dicistro-like viruses and 13 untypeable viruses. Many partial picorna-like virus sequences up to 10.2 kb were also investigated. The sequences of the Havel picorna-like viruses represent genomes of seven of eight so far known Picornavirales families. Detection of numerous distantly-related dicistroviruses suggests the existence of additional, yet unexplored virus groups with dicistronic genomes, including few viruses with unusual genome layout. Of special interest is a clade of dicistronic viruses with capsid protein-encoding sequences at the 5'-end of the genome. Also, monocistronic viruses with similarity of their polymerase and capsid proteins to those of dicistroviruses are interesting. A second protein with NTP-binding site present in the polyprotein of solinviviruses and related viruses needs further attention. The results underline the importance to study the viromes of fluvial ecosystems. So far acknowledged marnaviruses have been isolated from marine organisms. However, the present study and available sequence data suggest that rivers and limnic habitats are relevant ecosystems with circulation of marnaviruses as well as a plethora of unknown picorna-like viruses.